The Local Wisdom of Madura in Ethnoparenting for Shaping Early Childhood Emotions - Trisetiawati, Jelita; Fadjryana Fitroh, Siti; Abdul Latif, Muhammad; Rashid Said Al Mushaiqri, Mahfouda; Venketsamy, Roy; Yuandana, Tarich (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2025)
Background of the study: Parenting styles are deeply influenced by cultural values and traditions. Ethnoparenting refers to parenting practices rooted in local wisdom and passed down through generations, which significantly shape children's emotional development. In Madura, particularly in the Bangkalan area, parenting practices are strongly embedded in local traditions, which influence how children learn to manage and express their emotions. However, research on the impact of Madurese ethnoparenting on early childhood emotional development remains limited. Aims and scope of paper: This study explores how Madurese ethnoparenting stimulates the emotional development of young children. It seeks to identify traditional parenting values and practices that contribute to children's emotional intelligence, including empathy, self-confidence, and social skills. Methods: This research utilizes a qualitative approach using a case study method in several Madurese families that implement ethnoparenting. Data collection was conducted through in-depth interviews, observations, and documentation. The collected data was then analyzed to identify recurring themes and patterns in ethnoparenting practices. Results: Findings indicate that ethnoparenting in Madura significantly contributes to early childhood emotional development. The practices of loving discipline, learning through cultural traditions, and emphasizing community values help children develop emotional regulation, social adaptability, and self-confidence. Parents instil emotional resilience by teaching respect, responsibility, and empathy through everyday interactions and traditional customs. Contribution: This research highlights the importance of integrating local wisdom into parenting to foster children's emotional growth. It emphasizes that parents, educators, and the community should preserve and adapt cultural values to enhance emotional intelligence in early childhood. Understanding the role of ethnoparenting can help shape policies and programs that support culturally responsive child development practices.